2023
DOI: 10.37285/ijpsn.2023.16.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety during Pregnancy: Current Consideration

Abstract: Food safety is critical during pregnancy. Pregnancy hormone changes reduce immune function, making pregnant women more vulnerable to food-borne illnesses. The unborn fetus is particularly sensitive to food-borne diseases since its immune system has not yet matured. Pregnant women must be extremely cautious about what they eat since they are eating not just for their health but also for the health of their unborn babies. When a pregnant woman eats well, she reduces her chances of anemia, low birth weight, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…Consumption of several delicious foods throughout different trimesters fulfills the satisfaction of pregnant women. [ 1 ] According to many surveys, it has been revealed that seasonal foods such as mango, jackfruits, palm in summer, different varieties of mushrooms and bamboo shoots in rainy and berries, and capsicums in winter are widely consumable food by pregnant women. Although many of these foods provide a completely healthy environment for fetus growth, several foods possess toxic moiety which may be harmful to developed fetus and lead to birth defects by a process teratogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of several delicious foods throughout different trimesters fulfills the satisfaction of pregnant women. [ 1 ] According to many surveys, it has been revealed that seasonal foods such as mango, jackfruits, palm in summer, different varieties of mushrooms and bamboo shoots in rainy and berries, and capsicums in winter are widely consumable food by pregnant women. Although many of these foods provide a completely healthy environment for fetus growth, several foods possess toxic moiety which may be harmful to developed fetus and lead to birth defects by a process teratogenicity.…”
Section: Introductionmentioning
confidence: 99%